PROPOSED MARKETING COMMUNICATION STRATEGY TO INCREASE INTENTION TO VISIT OF FOREIGN BACKPACKERS (CASE STUDY : CILETUH-PALABUHANRATU UNESCO GLOBAL GEOPARK (The Indonesian Journal of Business Administration, 2021)
Ciletuh-Palabuhanratu UNESCO Global Geopark (CPUGGp) are first West Java Geopark which located at Sukabumi regency region who possessed a UNESCO Global Geopark status in 2018. CPUGGp as a tourism destination, provides three geopark aspects for attract tourist such as : geodiversity, biodiversity, and cultural diversity. Although in 2018 CPUGGp has a highest visitors number for 1,175,258 visitors there is a declining drastically of 26% at 2019 who became 873,894 visitors compared to foreign visitor who came to Indonesia in 2019 CPUGGp still 1% of them. Theoritical approach in this research are using customer analysis, external analysis which conduct general environment (PESTEL) and industry environment (Porter 5 Forces) and also internal analysis which conduct resources based model. Methodology uses for customer analysis is using multiple regression analysis. Self development, cultural & heritable knowledge, meet and interact with local people, mixing with fellow backpackers, excitement, and relaxation are independent variables which presents foreign backpackers motivation, while intention to visit is the dependent variable. Based on multiple regression analysis of SPSS 23, the results that influenced intention to visit were found to self development, cultural & heritable knowledge, mixing with fellow backpackers, and relaxation. The results of this analysis will be develop into integrated marketing communication strategy to reach backpackers motivation that expected to improve to increase their intention to visit CPUGGp. Keywords: backpacker motivation, intention to visit, linier regression, marketing communication.